Borderline personality disorder in transition age youth with bipolar disorder. (11th April 2015) - Yen, S.; Frazier, E.; Hower, H.; Weinstock, L. M.; Topor, D. R.; Hunt, J.; Goldstein, T. R.; Goldstein, B. I.; Gill, M. K.; Ryan, N. D.; Strober, M.; Birmaher, B.; et al.
Abstract : Objective: To determine the longitudinal impact of borderline personality disorder (BPD) on the course and outcome of bipolar disorder (BP) in a pediatric BP sample. Method: Participants ( N  = 271) and parents from the Course and Outcome of Bipolar Youth (COBY) study were administered structured clinical interviews and self‐reports on average every 8.7 months over a mean of 93 months starting at age 13.0 ± 3.1 years. The structured interview for DSM‐IV personality disorders (SIDP‐IV) was administered at the first follow‐up after age 18 to assess for symptoms of BPD. BPD operationalized at the disorder, factor, and symptom level, was examined as a predictor of poor clinical course of BP using all years of follow‐up data. Results: The number of BPD symptoms was significantly associated with poor clinical course of BP, above and beyond BP characteristics. Affective dysregulation was most strongly associated with poor course at the factor level; the individual symptoms most strongly associated with poor course were dissociation/stress‐related paranoid ideation, impulsivity, and affective instability. Conclusion: BPD severity adds significantly to the burden of BP illness and is significantly associated with a more chronic and severe course and outcome beyond what can be attributable to BP characteristics.